Analysis of Competitive Strategy Innovations: Case A Course and Training Institutes AHA Smart Matematika Jakarta - Rohilah Rohilah; Erry Sunarya; R Deni Muhammad Danial (International Journal of Economics (IJEC), 2023)
This study aims to find out and explain the innovation strategies taken by LKP aha smart Mathematics. This research method is qualitative, namely, the research procedure produces descriptive data, both in the form of speech, behavior, and phenomena found when jumping directly into the field to observe the Objects and Subjects to be studied. The data collection technique is carried out through observation, interviews, and documentation. Data analysis is carried out by selecting answers obtained from informants and then collected for analysis and conclusions. The data analysis used is data triangulation. The results of the research were obtained, competitive strategy innovations taken by aha smart mathematics course and training institutions using Michael E Porter's generic strategy, namely low-cost strategies: the fees set by the smart mathematics course and training institutions are Rp 250,000 / month for regular, and Rp 300,000 / month for intensive, differentiation strategies: aha smart mathematics course and training institutions create a unique method that is a differentiator from other LKPs that Similar, and strategy focus: AHA Smart Mathematics course and training institutions focus on market segmentation, focus on optimal products and services, and focus on organizational structuring.